Macro-Micro Feedback Links of Irrigation Water Management In Turkey - Çakmak, Erol H. 1992- (The World Bank, 2008)
Agricultural production is heavily dependent on water availability in Turkey, where half the crop production relies on irrigation. Irrigated agriculture consumes about 75 percent of total water used, which is about 30 percent of renewable water availability. This study analyzes the likely effects of increased competition for water resources and changes in the Turkish economy. The analysis uses an economy-wide Walrasian Computable General Equilibrium model with a detailed account of the agricultural sector. The study investigated the economy-wide effects of two external shocks, namely a permanent increase in the world prices of agricultural commodities and climate change, along with the impact of the domestic reallocation of water between agricultural and non-agricultural uses. It was also recognized that because of spatial heterogeneity of the climate, the simulated scenarios have differential impact on the agricultural production and hence on the allocation of factors of production including water. The greatest effects on major macroeconomic indicators occur in the climate change simulations. As a result of the transfer of water from rural to urban areas, overall production of all crops declines. Although production on rainfed land increases, production on irrigated land declines, most notably the production of maize and fruits. The decrease in agricultural production, coupled with the domestic price increase, is further reflected in net trade. Agricultural imports increase with a greater decline in agricultural exports